Effects of dietary sports supplements on metabolite accumulation, vasodilation and cellular swelling in relation to muscle hypertrophy: A focus on secondary physiological determinants - Cholewa, Jason; Trexler, Eric; Lima-Soares, Fernanda; Pessoa, Kassiana de Araij; Sousa-Silva, Rayssa; Santos, Azenildo Moura; Zhi, Xia; Nicastro, Humberto; Torres Cabido, Christian Emmanuel; Freitas, Marcelo Conrado de [UNESP]; Rossi, Fabricio; Zanchi, Nelo Eidy (Elsevier B.V., 2019)
Increased blood flow via vasodilation, metabolite production, and venous pooling contribute to the hyperemia and cellular swelling experienced during resistance training. It has been suggested that these effects play a role in hypertrophic adaptations. Over the past 2 decades, sport supplement products have been marketed to promote exercise hyperemia and intracellular fluid storage, thereby enhancing hypertrophy via acute swelling of myocytes. The three main classes of supplements hypothesized to promote exercise-induced hyperemia include vasodilators, such as nitric oxide precursor supplements: anaerobic energy system ergogenic aids that increase metabolite production, such as beta-alanine and creatine; and organic osmolytes, such as creatine and betaine. Previous studies indicated that these dietary supplements are able to improve muscle performance and thus enhance muscle hypertrophy; however, recent evidences also point to these three classes of supplements affecting secondary physiological determinants of muscle mass accretion such as vasodilation, metabolite accumulation, and muscle cellular swelling. Although we recognize that the literature is relatively scarce regarding these topics, a better comprehension and discussion of these determinants can lead to increased knowledge and might guide further research regarding the proposed mechanisms of action of the identified compounds. In this case, increased knowledge may contribute to the development of improved efficacy, new products, or direct new research to specifically investigate those secondary effects. The aim of this review was to bring into focus new perspectives associated with secondary physiological effects induced by supplementation and to determine their relevance. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Ergogenic aids; Beetroot juice; Vasodilation; Betaine; Creatine; Beta-alanine